Structural Change, Fundamentals, and Growth: A Framework and Case Studies - McMillan, Margaret S.; McMillan, Margaret S.; Rodrik, Dani; Sepúlveda, Claudia (2017)
Margaret McMillan IFPRI BOOK LAUNCH Structural Change, Fundamentals, and Growth: A Framework and Case Studies Edited by Margaret McMillan, Dani Rodrik, and Claudia Sepúlveda MAY 11, 2017 - 12:15 PM TO 01:45 PM EDT